The Effect of Perineal Massage on The Spontaneous Perineal Rupture in Maternity Mothers - Sri Faulindawati; Anni Suciawati; Febry Mutiariami Dahlan (Rajaki of Tulip Medika Publisher, 2023)
Background: Perineal rupture is the main cause of postpartum maternal bleeding. Postpartum bleeding is the main cause of 40% of maternal deaths in Indonesia. The number of cases of maternal deaths decreased from 4,999 in 2015 to 4912 in 2016. Perineal rupture is caused by parity, birth spacing, infant weight, labor delivery, cunam extraction, vacuum extraction, tool trauma and episiotomy. Purpose: The aim was to examine the effect of perineal massage on spontaneous perineal rupture among labor mother at the Paramitra Medika 1 Clinic in intervention and control groups. Methods: This research was used pre-experiment by using static group comparison. The sample size was 30 labor mother who consisted of 15 in the experimental group and 15 in the control group. Observation form as an instrument. Univariat and bivariate variable were used and used paired t-test with alpha 0,05. Result: The results showed that 60.0% of mothers given perineal massage did not experience perineal rupture, the average rupture was 1.47 with a standard deviation of 0.64 and as many as 46.7% of mothers who were not given perineal massage had a secon degree rupture, on average rupture is 1.40 with a standard deviation of 0.986. Perineal massage has an effect on the spontaneous perineal rupture in maternal (p value 0.008). Conclusion: It was expected that further study, such as sample are pregnant women so that the massage results are not different.